1996
DOI: 10.1002/art.1780390704
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐range and dose‐frequency study of recombinant human interleukin‐1 receptor antagonist in patients with rheumatoid arthritis

Abstract: Objective. To preliminarily evaluate the safety and efficacy of different dose levels and dosing frequencies of recombinant human interleukin-1 receptor antagonist (rHuIL-1Ra) in the treatment of patients with rheumatoid arthritis (RA).Methods. One hundred seventy-five patients with active RA were enrolled in a randomized, double-blind trial of rHuIG1Ra administered by subcutaneous injection. There were 9 treatment groups in the trial. During the initial 3-week treatment phase, patients were treated with 20, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
114
0
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(125 citation statements)
references
References 21 publications
4
114
0
7
Order By: Relevance
“…15,17 The efficacy of recombinant human IL-1Ra in the treatment of active RA was confirmed in long-term placebo-controlled clinical studies. 11,12 Recently, recombinant human IL-1Ra protein was approved for the treatment of active RA. However, because of the chronic characteristics of autoimmune arthritis, daily subcutaneous injection of 100 mg IL-1Ra is generally required to obtain a clinically significant benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17 The efficacy of recombinant human IL-1Ra in the treatment of active RA was confirmed in long-term placebo-controlled clinical studies. 11,12 Recently, recombinant human IL-1Ra protein was approved for the treatment of active RA. However, because of the chronic characteristics of autoimmune arthritis, daily subcutaneous injection of 100 mg IL-1Ra is generally required to obtain a clinically significant benefit.…”
Section: Discussionmentioning
confidence: 99%
“…1,[6][7][8][9][10] Several independent clinical trials have been completed in which the recombinant IL-1Ra protein has been administered for a long-term period to patients with RA. 11,12 The results indicate that treatment with IL-1Ra lowers the levels of proteins involved in the acute phase of RA and the counts of swollen joints and, furthermore, may inhibit radiographic progression of the disease. 12,13 Recently, the use of recombinant human IL-1Ra protein was approved for the treatment of human RA.…”
Section: Introductionmentioning
confidence: 97%
“…Although IL-1 and TNF␣ share many biologic actions that are relevant in RA (4)(5)(6), research in animal models of arthritis suggests that IL-1 is the dominant cartilagedestructive cytokine (7). The biologic effects of both cytokines are modulated in vivo by naturally occurring protein inhibitors (8,9), and both have become prime targets for biologic therapy in RA (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Following the demonstration of short-term efficacy and safety in a preliminary double-blind, doseranging study in patients with RA (15), the safety and efficacy of daily SC injections of anakinra was confirmed in a large, multicenter, placebo-controlled, 24-week study (16). In addition to demonstrating significant improvements in the American College of Rheumatology (ACR; formerly, the American Rheumatism Association) composite index (22) and the Paulus 20% criteria (23), this study also provided evidence of retardation in the rate of radiographically observed structural damage (16,24).…”
mentioning
confidence: 99%
“…[1][2][3][4] Rheumatoid arthritis (RA) is a systemic autoimmune disOne difficulty with using proteins as therapeutic ease characterized by chronic inflammation of the joints. agents for RA is the inability to deliver the protein to the The onset of RA is insidious, but its course is progressive.…”
Section: Introductionmentioning
confidence: 99%